KATA 'SĀFĀR' DALAM PERSPEKTIF SUFI: KAJIAN TERHADAP METAFORA KONSEPTUAL GEORGE LAKOFF - Chaer, Hasanuddin; Rasyad, Abdul; Mari'i, Mari'i; Hidayat, Rahmat; Susanti, Pipit Aprilia; Riyanto, Andra Ade (Lingua Franca:Jurnal Bahasa, Sastra, dan Pengajarannya, 2024)
This article delves deeply into the essence of the word 'Sāfār' from a Sufi perspective, utilizing the conceptual metaphor framework developed by George Lakoff. The research aims to uncover the philosophical and spiritual meanings contained within the word 'Sāfār' in the context of Sufi tradition, and how the use of conceptual metaphor can deepen our understanding of Sufi mystical journeys. Within Lakoff's "The Path Traversed-If Possible/Not Possible" conceptual framework, the article explores the dynamics between the Source Domain and the Target Domain in the metaphor of 'Sāfār'. This research applies George Lakoff's conceptual metaphor method to interpret the literal meaning of the word 'Sāfār' within the spiritual Sufi framework into a metaphorical meaning. To understand this phenomenon, the research is conducted through three stages: First, data collection, in which researchers gather literal words of 'Sāfār' from the texts of the Qur'an and Sufi manuscripts. Second, data analysis, in which researchers observe, analyze, and understand the literal meaning of the word 'Sāfār' in the Qur'anic texts, and connect it with metaphorical meanings. Third, data conclusion, where researchers understand and interpret the meaning from the source domain to the target domain of the metaphor of the word 'Sāfār' in the context of Sufi spiritual journey. Findings from this research indicate that a metaphorical understanding of the term 'Sāfār' can provide new insights and broader perspectives on spiritual, philosophical, and cognitive linguistic experiences. This is because the research highlights the complexity of dynamics between the source domain and the target domain in the process of metaphorical interpretation.